Нормальное строение группы локальных изометрий границы сферически однородного дерева - Лавренюк, Я.В.; Сущанский, В.И. (Видавничий дім "Академперіодика" НАН України, 2007)
The normal structure of the locally isometry group LIsom ∂T of a spherically homogeneous tree boundary is investigated. It is proved that every closed normal subgroup of this group contains a commutant of LIsom ∂T. The quotient of LIsom ∂T by its commutant is found.